Effect of TiO2 and Al2O3-ethylene glycol-based nanofluids on cutting temperature and surface roughness during turning process of AISI 1018 - Zetty Akhtar, A. M.; M. M., Rahman; K., Kadirgama; Maleque, M. A. (IOP Publishing, 2020)
This paper presents the effect of TiO2 and Al2O3-ethylene glycol based nanofluids on cutting temperature and surface roughness during turning process of AISI 1018. Minimum quantity lubrication (MQL) method has been recognized in minimizing the usage of cutting fluid, as a step to achieve cleaner environment and sustainable machining. However, the low thermal conductivity of base fluid in minimum quantity lubrication system caused the insufficient removal of heat generated in cutting zone. Addition of nanoparticles to the base fluid was then introduced to enhance the performance of cutting fluids. In this study, the machinability of AISI 1018 (mild steel) was investigated under dry machining and nanofluid minimum quantity lubrication method. Two types of nanofluids (TiO2 and Al2O3 nanofluid) with concentration 0.05, 0.15 and 0.3 wt.% were used in this study. The experiments were conducted on lathe machine, using tungsten carbide as cutting tool. Three cutting speed (350,550 and 750 m/min), three depth of cut (0.5, 1.0 and 1.5 mm) and fixed minimum quantity lubrication system nozzle pressure (5 bar) were applied throughout turning operation. To determine the relationship between machining parameters and cutting temperature and surface roughness values were measured. Based on results obtained, the cutting temperature of workpieces with usage of nanofluids in MQL system gave lower value compared to dry machining. The surface roughness of machined parts was also improved under NFMQL methods. In conclusion, when the nanofluid-MQL method was employed, the amount of cutting fluid was reduced and machining performance improved.